2015
DOI: 10.1177/0194599815581832
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Dysphonia in Patients with Cystic Fibrosis

Abstract: Objective To assess the prevalence and severity of dysphonia in patients with cystic fibrosis sinusitis. We hypothesized that patients with CF sinusitis, compared with 2 control groups, would have higher self-reported prevalence of dysphonia and greater severity of dysphonia, according to patient-reported outcome measures as well as auditory-perceptual evaluation by expert listeners. Study Design Cross-sectional comparative pilot study. Setting Academic tertiary care clinic. Study Participants and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…Such data agree with those previously described by Willis et al. 20 that found a mean value of 33.9 ± 16.8 points in 17 patients with CF and CRS and a value of 39.1 ± 19.9 points in 10 patients with CRS, not due to CF. Thus, despite the presence of CRS, patients with CF had a low value of SNOT-22 as compared to other groups of patients with CRS, 16 and these data confirm that CF patients do not feel the severity of sinus alterations because of the early onset of CRS in childhood and because sinus symptoms are masked by the severity of other medical issues.…”
Section: Discussionsupporting
confidence: 93%
“…Such data agree with those previously described by Willis et al. 20 that found a mean value of 33.9 ± 16.8 points in 17 patients with CF and CRS and a value of 39.1 ± 19.9 points in 10 patients with CRS, not due to CF. Thus, despite the presence of CRS, patients with CF had a low value of SNOT-22 as compared to other groups of patients with CRS, 16 and these data confirm that CF patients do not feel the severity of sinus alterations because of the early onset of CRS in childhood and because sinus symptoms are masked by the severity of other medical issues.…”
Section: Discussionsupporting
confidence: 93%
“…Evaluation of subjective symptoms in our CF‐population of 124 patients revealed a mean total SNOT‐20 score of 15.2 ± 12.1 pts. Willis et al found that SNOT scores from non‐CF patients with sinusitis (39.1 ± 19.9 pts) were higher than those reported by CF patients (33.9 ± 16.8 pts), whereas scores in his healthy controls resulted to be significantly lower (5.2 ± 5.4 pts) . Accordingly, prevalences of chronic rhinosinusitis in CF patients accord for 11–72% of patients assessed in recent studies .…”
Section: Discussionmentioning
confidence: 94%
“…The Sino-Nasal Outcome Test-20 (SNOT-20) questionnaire was used to assess HQOL more specifically related to the sino-nasal outcome. It has been validated in patients with chronic rhinosinusitis [ 31 , 32 ], and used to assess sino-nasal outcome in relation to other diseases such as asthma [ 33 ], cystic fibrosis [ 34 ], skull base tumors [ 35 ] and in healthy individuals [ 33 ].…”
Section: Methodsmentioning
confidence: 99%